Mandatory HIV/AIDS testing as an additional precondition for the management of the HIV/AIDS pandemic : a South African women’s human rights perspective - Gobind, Jenika (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Industrial Psychology))--University of Stellenbosch, 2009.